Di-(2-ethylhexyl) Phthalate Promotes Allergic Lung Inflammation by Modulating CD8α+ Dendritic Cell Differentiation via Metabolite MEHP-PPARγ Axis - Tseng, Hsin-Han; Li, Chia-Yang; Wu, Shin-Ting; Su, Hsiang-Han; Wong, Tzu-Hsuan; Wu, Hsin-En; Chang, Yu-Wei; Huang, Shau-Ku; Tsai, Eing Mei; Suen, Jau-Ling (Frontiers in Immunology, 2022)
Di-(2-ethylhexyl) phthalate (DEHP), a common plasticizer, is a ubiquitous environmental pollutant that can disrupt endocrine function. Epidemiological studies suggest that chronic exposure to DEHP in the environment is associated with the prevalence of childhood allergic diseases; however, the underlying causal relationship and immunological mechanism remain unclear. This study explored the immunomodulatory effect of DEHP on allergic lung inflammation, while particularly focusing on the impact of DEHP and its metabolite on dendritic cell differentiation and activity of peroxisome proliferator-activated receptor gamma (PPARγ). The results showed that exposure to DEHP at a human tolerable daily intake dose exacerbated allergic lung inflammation in mice. Ex vivo flow cytometric analysis revealed that DEHP-exposed mice displayed a significantly decreased number of CD8α+ dendritic cells (DCs) in spleens and DC progenitors in the bone marrow, as well as, less interleukin-12 production in splenic DCs and increased T helper 2 polarization. Pharmacological experiments showed that mono-(2-ethylhexyl) phthalate (MEHP), the main metabolite of DEHP, significantly hampered the differentiation of CD8α+ DCs from Fms-like tyrosine kinase 3 ligand-differentiated bone marrow culture, by modulating PPARγ activity. These results suggested that chronic exposure to DEHP at environmentally relevant levels, promotes allergic lung inflammation, at least in part, by altering DC differentiation through the MEHP-PPARγ axis. This study has crucial implications for the interaction(s) between environmental pollutants and innate immunity, with respect to the development of allergic asthma.